THE ACHIEVEMENT OF PROJECTILE MOTION CONCEPT IN THE SMA MUHAMMADIYAH 2 YOGYAKARTA’S STUDENTS - Hidayatulloh, Wahyu (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2020)
This research is a qualitatif research that aims to know to what extend the student’s performance in achieving Projectile Motion concept in the SMA Muhammadiyah 2 Yogyakarta’s students. The methods used in this research was questionnaire and interview to the Physics Teacher. The subjects of this reseach were 40 students of X grade. Based on the result of the research we can conclude that the performance of student’s understanding of Uniform Linear Motion and Accelerated Linear Motion, fundamental trigonometry, and conservation of energy are still need to be increased because these concepts were very important to be achieved to help students understand the concept of Projectile Motion in Physics.